2014
DOI: 10.1016/j.ajpath.2014.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Expression of the Human MRP2 Transporter Reduces Cisplatin Accumulation and Nephrotoxicity in Mrp2-Null Mice

Abstract: The chemotherapeutic drug cisplatin is actively transported into proximal tubules, leading to acute renal injury. Previous studies suggest that the multidrug resistance-associated protein 2 (Mrp2) transporter may efflux cisplatin conjugates from cells. We sought to determine whether the absence of Mrp2 alters the accumulation and toxicity of platinum in the kidneys of mice and whether transgenic expression of the human MRP2 gene could protect against cisplatin injury in vivo. Plasma, kidneys, and livers from v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 40 publications
0
38
0
Order By: Relevance
“…It is known from the literature that decreasing MRP2 levels result in increased proximal tubule injury [14]. We show here for the first time the correlation between ET-1-induced miRNA 133a overexpression, proteinuria, and decreasing MRP2 levels, which results in nephrotoxicity.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…It is known from the literature that decreasing MRP2 levels result in increased proximal tubule injury [14]. We show here for the first time the correlation between ET-1-induced miRNA 133a overexpression, proteinuria, and decreasing MRP2 levels, which results in nephrotoxicity.…”
Section: Introductionmentioning
confidence: 55%
“…3), we propose that MRP2 is functionally inactivated in proteinuric disease, contributing to proximal tubular damage. This observation is strengthened by experiments in MRP2 knockout mice showing a more extensive proximal tubule injury [14]. …”
Section: Discussionmentioning
confidence: 84%
“…In addition, our cell models and CDDP studies (as in (39, 40)) have not observed a clear contribution of MRP1 (and MDR1) to cell survival in the context of alkylating drugs. On the other hand, MRP2 (which is low expressed in MDA-MB231 and U2OS cells) increased CDDP-glutathione conjugates efflux and decreased kidney injury in mice (41). Regarding the antioxidant role of GSH, alkylating agents are well-known inducers of ROS production (6, 42, 43), although our data and data from others (43) are contending that the contribution of ROS to toxicity is minor; likely a secondary phenotype consequent to GSH depletion.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic expression of the human MRP2/ABCC2 gene in Mrp2-null mice reduced the accumulation of platinum in the kidneys to levels observed in wild-type mice without altering plasma platinum levels. Nephrotoxicity was also reduced in humanized MRP2 mice compared to Mrp2-null mice [291]. These data show direct in vivo evidence of the involvement of MRP2 in the efflux of platinum species and nephroprotection.…”
Section: Prototypical Nephrotoxicantsmentioning
confidence: 79%
“…More recently, Wen et al . (2014) found that cisplatin inhibited transport of the MRP2/Mrp2 substrate 5(6)-carboxy-2′,7′-dichlorofluorescein by 70 to 80% in vesicles expressing mouse Mrp2 and human MRP2 [291]. Furthermore, Mrp2-null mice treated with cisplatin exhibited 2-fold higher BUN levels, a greater increase in SCr concentration, and more severe proximal tubule degeneration and necrosis compared to wild-type mice.…”
Section: Prototypical Nephrotoxicantsmentioning
confidence: 99%